Kurikulum Merdeka Belajar Merujuk Pengembangan Kurikulum Abad 21 Di SMK NEGERI 1 Sungai Rotan - Neta Dian Lestari; Nova Pratiwi; Chandra Kurniawan; Januardi Januardi; Riswan Aradea; Masnunah Masnunah; Nurlina Nurlina; Aswadi Jaya; Amin Rohmat; Dea Khusnul Khotimah (Universitas PGRI Palembang, 2022)
The purpose of the implementation as the main task of the Tri Dharma of Higher Education is the realization of the work program of the Accounting Education study program. The main purpose of this community service is to socialize and improve the quality of learning with Project Actualization and Blended Learning in 21st Century learning and understanding in preparing superior Indonesian human resources with the Independent Learning Curriculum. The results of community service activities with PKM Kurikulum Merdeka friends Learning Referring to 21st Century Curriculum Development At SMK Negeri 1 Sungai Rotan have been carried out very well, effectively, and by the expectations desired by community service participants.